Formation of Gender Culture of Future Border Guard Officers in the Course of Their Professional Training as a Pedagogical Problem - Kusiak, Liudmyla (Pedagogical Discourse, 2022)
The educational system of Ukraine has been under significant changes recently. The transformations are largely determined by the full-scale Russian invasion of Ukraine that has also streamlined the European and NATO integration processes in the country. Being a democratic society, Ukraine seeks to share principles and standards based on gender equality and non-discrimination. Therefore, we have defined that it is vital to study the means necessary to overcome gender stereotypes, integrate gender responsive content in educational processes and create gender sensitive educational environment. This would contribute to introducing effective forms and methods required to forge gender culture of future border guard officers. Based on the analysis of scientific views of national and international scientists, the article focuses on the need and importance of studying the problem of the formation of gender culture in a higher military educational establishment. National Academy of the State Border Service of Ukraine named after Bohdan Khmelnytsky is a unique border guard higher military educational institution in Ukraine where future border guard officers are trained to detect, identify and combat security threats at the border, especially while ensuring the protection of human rights and freedoms of border crossers. Taking into account that the formation of gender culture of the future border guard officers in the course of their professional training is a pedagogical problem, we offer some steps to tackle the problem. Moreover, the article gives a comprehensive overview on how the obtained results are to be applied in practice. It is anticipated to create an elaborate cycle of classes for English Language Learning Course based on interactive forms and methods of teaching gender responsive content. We aim to involve cadets into research and educational activities so that they could learn more about the nature of gender-related issues, be able to tackle such issues if they occur and participate in advancing the policy of gender equality and nondiscrimination among their peers, etc.